The Effect of Ethnic Variation on the Success of Induced Labour in Nulliparous Women with Postdates Pregnancies - Dimitrios Papoutsis; Angeliki Antonakou; Chara Tzavara (Scientifica)
Objective. To identify the potential effect of ethnic variation on the success of induction of labour in nulliparous women with postdates pregnancies. Study Design. This was an observational cohort study of women being induced for postdates pregnancies (≥41 weeks) between 2007 and 2013. Women induced for stillbirths and with multiple pregnancies were excluded. The primary objective was to identify the effect of ethnicity on the caesarean section (CS) delivery rates in this cohort of women. Results. 1,636 nulliparous women were identified with a mean age of 27.2 years. 95.8% of the women were of White ethnic origin, 2.6% were Asian, and 1.6% were of Black ethnic origin. The CS delivery rate was 24.4% in the total sample. Women of Black ethnic origin had a 3.26 times greater likelihood for CS in comparison to White women, after adjusting for maternal age, BMI, smoking, presence of meconium, use of epidural analgesia, fetal gender, birth weight, and head circumference (adjusted OR = 3.26; 95% CI: 1.31–8.08, p = 0.011). Conclusion. We have found that nulliparous women of Black ethnicity demonstrate an almost threefold increased risk of caesarean section delivery when induced for postdates pregnancy.